Analisis Kesediaan Membayar (Willingness To Pay) Konsumen Terhadap Pembelian Sayur Kangkung (Ipomoea Reptans Poir) Hidroponik Dan Faktor-Faktor Yang Mempengaruhinya (Studi Kasus: Konsumen Analisa Agrokreasi (AAK), Kecamatan Medan Johor) - Mestika Amelia Sinuraya; Muhammad Ilham Riyadh; Violeta Tia Monica (Journal of Innovative and Creativity, 2025)
Some people choose food not only to fulfill basic needs, but also as an effort to ensure their health. Therefore, it is important to understand the extent to which consumers are willing to pay (Willingness To Pay) for a product, because this information can help producers understand consumers. The aims of this research are: 1). To find out the characteristics of consumers of hydroponic kale vegetables. 2).To find out the maximum value that consumers are willing to pay to obtain hydroponic kale vegetables. 3). To find out what factors influence consumers' willingness to pay for hydroponic kale vegetables. This research applies a survey method as an approach to collecting data by conducting direct inspections in the field or research location. This research was carried out in Acrocreation Analysis, with the location chosen purposively. The number of samples used in this research was 43 samples. The data collected in this research is divided into two sources, namely: Primary and secondary data. The data processing and analysis methods applied include descriptive analysis, linear regression analysis, and the application of CVM (Contingent Valuation Method). The software used for the analysis is Microsoft Excel 2010 and SPSS version 26. The results of the research show that the average WTP value of consumers in AAK is IDR 6,302.32/pack and the factor that has a real influence on consumers' willingness to pay for hydroponic kale among AAK consumers is the length of time they consume it. (X5). Meanwhile, factors that have no real influence are age (X1), education level (X2), income (X3) and number of family dependents (X4).